OP142 Reviewing Methods For Early Assessment. (2019) - Stome, Linn Nathalie; Moger, Tron; Kidholm, Kristian; Kvaerner, Kari
Abstract : Introduction: The project DigiHelse aims to support the municipality health in Norway by offering a digital communication platform to users of the home care service nationally. In a concept stage of innovation, an early assessment of the potential socioeconomic value of the project was carried out by means of stakeholder insight and scenario drafting. As the assessment showed favorable potential in providing decision support and reducing risk, the project received funding to move into the pilot phase. The objective of this study is to reassess the effect of stakeholder insight and scenario drafting by validating the results using empirical data from the first pilot of DigiHelse. Methods: Through collecting empirical data on resource consumption and inquiries to the service from four intervention districts and one control district in Oslo, the socioeconomic value of DigiHelse was reassessed. In addition to survey and register data collected before and after the pilot, behavioral data was introduced as a new data source. Results: The effect of early assessment by means of stakeholder insight and scenario drafting was successfully studied adding empirical data from the projects first pilot. The real-time data on user behavior registered in the DigiHelse server contributed to verify the assumptions from the first assessment of the project. Although the results from the analysis were less optimistic than the first assessment, the study revealed important improvement measures necessary to improve the innovation process. Conclusions: The usefulness of early assessment is questioned, due to lack of precision of estimates caused by scarce available data. The present study presents a first step in evaluating the precision of employing stakeholder insight and scenario drafting as additional information in early assessment of innovation. The studied approach to early assessment showed potential in enhancing decision support and reducing risk from a concept stage of innovation.